COMPARATIVE INVITRO ACTIVITY OF 3 CEPHALOSPORINS AGAINST STAPHYLOCOCCUS-AUREUS ISOLATED FROM BOVINE MASTITIS - Lopes, CAM; Moreno, G. (British Veterinary Assoc, 1991)
This report compares the in vitro activity of three cephalosporins (cephalothin, cefoxitin and ceftriaxone) against 57 Staphylococcus aureus strains isolated from cows with clinical mastitis on the basis of the minimal inhibitory (MIC) and minimal bactericidal concentrations (MBC). The majority of the S aureus strains showed resistance to cefoxitin and ceftriaxone and sensitivity to cephalothin. The highest MICs and MBCs were found for cefoxitin and ceftriaxone. Antimicrobial tolerance (MBC/MIC greater-than-or-equal-to 32:1) was observed in relation to cephalothin and ceftriaxone. The data suggest that these cephalosporins may not be effective for the treatment of staphylococcal bovine mastitis. The precise definition of their antimicrobial efficacies requires more detailed in vitro and in vivo studies.